Effect of Hypothyroidism on Cognitive Status: Evidence from Stroop Task - Shilpi Goyal; Abhinav Dixit; Neelam Vaney; S. V. Madhu (Indian Journal of Medical Specialities)
Background: Very less work has been done in the past to assess cognition in hypothyroid patients using classical color-word Stroop task. The Stroop color-word task is a well-recognized tool which estimates cognitive inhibition. Stroop task is based on the fact that reading words and identifying color of written words are two different information and they process with a common response channel but with different speeds. The aim of this study was to assess the cognitive inhibition process in drug-naïve hypothyroid patients and their comparison with the same patients after the attainment of euthyroid status and also with euthyroid controls using classical color-word Stroop task. Materials and Methods: Thirty drug-naïve newly diagnosed hypothyroid patients were study cases who underwent Stroop task once before initiating treatment and then after the attainment of euthyroid state. We performed the same test in euthyroid controls twice at an interval of 3 months for comparison purpose. Correlation analysis was also done for hypothyroidism and cognition. Results: The reaction time of Stroop task was decreased in all the three conditions of each block, i.e., neutral, incongruent, and congruent conditions after the attainment of euthyroid state, and the finding confirms posttreatment modulation of the attention processes in hypothyroid patients. Reaction time of Stroop task in hypothyroid patients was positively correlated with the serum thyroid-stimulating hormone levels. Processing of color identification was suppressed than reading words in hypothyroid patients as evidenced by increased reaction time of Stroop task. This increase in reaction time can be reversed by earlier identification of drug-naïve hypothyroid cases so that they can get timely treatment to restore their cognitive status. Conclusions: Stroop task scores are reduced in overt hypothyroid patients, but improve after thyroid replacement therapy.